The Effective Factors on Knowledge Management in Universities from Physical Education Instructors' Viewpoints - Shafiee Shahram; Eskandaripour Mojtaba; Soltani Samira (Sciendo, 2020)
The aim of the present study was to investigate the relation of technology, organizational culture and emotional intelligence with knowledge management using the mediators of organizational structure and empowerment. The methodology of the research was descriptive-correlational and the population of the study consisted of all the physical education instructors of Zanjan universities with three-year teaching record (61 people). The population size using the census sample criterion. Research tool included Stankosky and Baldanza's technology, organizational culture and structure, Bar-On's emotional intelligence inventory, Spreitzer and Mishra's empowerment, Kordnaij et al. and Newman and Conrad's knowledge management framework questionnaires. The structural equation modelling was used via Smart PLS 2 software for analyzing the data. The results showed that there is a negative and significant relation between technology and knowledge management. Also, there is significant relation between organizational culture and knowledge management, emotional intelligence and knowledge management, technology and organizational structure, organizational culture and organizational structure, technology and empowerment, organizational culture and empowerment, organizational structure and empowerment and empowerment and knowledge management; while the significance of relations between organizational structure and knowledge management and emotional intelligence and empowerment were not confirmed. The results of the present study can help the people in charge of education and research in the universities in order to produce, keep and use the needed knowledge related to proper time and place by making decisions and educating people.